Adolescents' level of knowledge of and supportive attitudes to sexual crime in the Swedish context. Issue 2 (4th May 2019) - Svensson, Jessika; Baer, Nina; Silva, Teresa
ABSTRACT: The aim of the present study was twofold. First, we wanted to quantify the level of knowledge of Swedish young people regarding sexual crime and to evaluate their supportive attitudes, while at the same time we aimed at identifying, through self-report, the sources that most contribute to such knowledge and attitudes. A sample of 245 upper secondary school students was selected from five schools in four Swedish counties. The results indicate that adolescents in Sweden have a high level of knowledge of rape, sexual molestation/harassment, and sexual exploitation of a dependent person. Furthermore, they show non-supportive attitudes to rape, sexual harassment, and sexual crime in general. However, some issues related to these types of crime proved to be confusing to the participants and, therefore, require targeting in education policies, specifically among juvenile males and those born abroad. The results are discussed in the context of the needs for sexual crime prevention.